1983
DOI: 10.1136/adc.58.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypothyroidism and the low T3 syndrome in thalassaemia major

Abstract: SUMMARY Basal thyroid function was assessed from the serum thyroxine, triiodothyronine, and thyroid-stimulating hormone concentrations in 1 14 patients (mean age 13 * 6 years), designated group 1, with thalassaemia major. Forty of these patients were further evaluated (group 2) for serum-free thyroxine, and free and reverse triiodothyronine concentrations. The response of thyroid-stimulating hormone to thyrotrophin-releasing hormone was measured in 25 patients from this subgroup. Results were compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 23 publications
(5 reference statements)
4
25
0
4
Order By: Relevance
“…This is contrary to previous studies [71,72] including a 12-year longitudinal study by Filosa et al [72] 7 years earlier which showed no association between ferritin levels or transfusion statuswith worsening thyroid function. Some studies have reported a high prevalence of primary hypothyroidism reaching up to 17% -18% [7,73] whereas others have reported a low prevalence of 0% -9% [74,75]. Shamshirsaz et al [1] demonstrated a prevalence of 7.7% in their study similar to the Italian study group [35] who found 6.2% patients to be hypothyroid where as Aydinok et al [47] showed the prevalence to be higher at 16%.…”
Section: Open Access Ojemdsupporting
confidence: 72%
See 2 more Smart Citations
“…This is contrary to previous studies [71,72] including a 12-year longitudinal study by Filosa et al [72] 7 years earlier which showed no association between ferritin levels or transfusion statuswith worsening thyroid function. Some studies have reported a high prevalence of primary hypothyroidism reaching up to 17% -18% [7,73] whereas others have reported a low prevalence of 0% -9% [74,75]. Shamshirsaz et al [1] demonstrated a prevalence of 7.7% in their study similar to the Italian study group [35] who found 6.2% patients to be hypothyroid where as Aydinok et al [47] showed the prevalence to be higher at 16%.…”
Section: Open Access Ojemdsupporting
confidence: 72%
“…It usually occurs in severely anaemic and/or iron overload thalassaemics but is uncommon in optimally treated patients [7,65]. The pathogenesis is again unclear but thought to relate to lipid perioxdiation, free radical release and oxidative stress [65].…”
Section: Open Access Ojemdmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside various causes, iron overload is an important, although rare etiological factor in thyroid failure 13,14 . The thyroid gland function in thalassaemia major has been reported to be normal, decreased reserve, or primary hypothyroidism.…”
Section: Table 1: Demographic Profile Of Study Populationmentioning
confidence: 99%
“…This endocrine complication is common in patients who are anaemic and/or poorly chelated (17%) but is rare in patients who are well treated [16]. Three types of thyroid dysfunction have been recognised: preclinical – the classical symptoms of hypothyroidism are absent; the serum FT4 is normal; TSH marginally increased and TSH response to TRH is increased; mild hypothyroidism growth retardation, tiredness and dry skin may be present, serum FT4 is marginally low whilst TSH is elevated and the TSH response to TRH is exaggerated.…”
Section: Hypothyroidismmentioning
confidence: 99%